Growth and mycoremediation activity of Panaeolus antillarum on lead-contaminated coconut water media - REYNANTE G. BUSTILLOS (Smujo International, 2026)
Abstract. Bustillos RG. 2026. Growth and mycoremediation activity of Panaeolus antillarum on lead-contaminated coconut water media. Asian J Agric 10: g100104. https://doi.org/10.13057/asianjagric/g100104. This study investigated the mycoremediation potential of lead (Pb) using the coprophilous mushroom Panaeolus antillarum cultivated in solid and liquid coconut water media. Mycelial growth performance, including mycelial diameter, dry biomass, and volume loss, was evaluated under different Pb concentrations of 1 ppm, 10 ppm, 100 ppm, and 1000 ppm using coconut water gulaman as solid medium and coconut water as liquid medium. In addition, Pb accumulation in the mycelia was quantified to assess bioaccumulation capacity. Statistical analysis showed that the highest mycelial diameter and thickness were recorded at 1 ppm Pb (77.0 mm), which was not significantly different from the control without Pb (79.50 mm). In contrast, no substantial mycelial growth was observed at 1000 ppm Pb, indicating strong inhibitory effects at high metal concentration. Among all Pb-contaminated treatments, the 1 ppm medium produced the highest mycelial biomass (1.82 g) and volume loss (8.52 mL). Maximum Pb bioaccumulation was significantly recorded at 100 ppm (268 mg/kg), whereas lower accumulation capacity was observed at reduced Pb concentrations, particularly at 1 ppm (11.0 mg/kg). Notably, the detectable Pb content in mycelia grown at 1000 ppm was attributed mainly to passive adsorption rather than active uptake, as excessive Pb levels severely suppressed biomass production. Overall, the observed tolerance to Pb stress and the ability to accumulate Pb indicate that P. antillarum exhibits substantial heavy metal resistance and mycoaccumulation potential, supporting its applicability in mycoremediation strategies for Pb-contaminated substrates.